Mercury(II) Complexes of Anionic N-Heterocyclic Carbene Ligands: Steric Effects of the Backbone Substituent - Dash, Chandrakanta (Molecules, 2020)
Mercury(II) complexes (Me-maloNHC(Dipp))HgCl (1b), (t-Bu-maloNHC(Dipp))HgCl (2b) and (t-Bu-maloNHC(Dipp))HgMe (2c) supported by anionic N-heterocyclic carbenes have been obtained in good yields from the reaction of the potassium salt of N-heterocyclic carbene ligand precursors and mercury(II) salts, HgCl(2) and MeHgI. These molecules have been characterized by (1)H-NMR, (13)C-NMR and IR spectroscopy and elemental analysis. X-ray crystal structures of 1b and 2b are also presented. Interestingly, complex 1b is polymeric {(Me-maloNHC(Dipp))HgCl}(n) in the solid state, as a result of inter-molecular Hg-O contacts, and features rare three coordinate mercury sites with a T-shaped arrangement, whereas the (t-Bu-maloNHC(Dipp))HgCl (2b) is monomeric and has a linear, two-coordinate mercury center. The formation of T-shaped structure and the aggregation of complex 1b is attributable to the reduced steric demand of the N-heterocyclic carbene ligand backbone substituent.